Range extension of Sanopus splendidus (Actinopterygii: Batrachoidiformes: Batrachoididae) in the Caribbean Sea - Moreno-Mendoza, Rigoberto (2019)
This paper records the presence of the splendid toadfish Sanopus splendidus Collete, Starck & Phillips, 1974, an endemic species from the Mexican Caribbean in two sampling sites in the Costa Occidental de Isla Mujeres, Punta Cancún y Punta Nizuc National Park (Mexico). Two subjects were photographed by sport divers. This is the northernmost record of this species in the Caribbean, broadening the known range by approximately 105 km from their type locality (Cozumel Island).